(untitled) (Journal of Parents and Teachers, 2014)
With the beginning of the year 2002, the media have tried to disseminate various calendars with multiple events. On the other hand, the United Nations have declared it the International Year of Mountains, which is why various educational activities are proposed, such as: - Studying the types of mountains and their origins. - Search for legends and myths about mountains. - Visiting exhibitions. In the article, you can discover more educational possibilities offered by this year.